Knowledge and practice of young schools on sexual and reproductive health - Francisca Isaelly dos Santos Dias, Maria Adelane Monteiro da Silva, Amanda Lourenço Tomaz, Ana Naiara Alves de Sousa (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8469-75